Combined influence of fluoride and biofilms on the biotribocorrosion behavior of titanium used for dental applications - Cruz, H. (2015)
Dental implant failures occur mainly due to biofilm infections and mastication micro-movements or load stresses that may induce wear degradation. Dental implants microgaps are highly susceptible areas for biofilm formation and fluoride retention. Although fluoride is an antimicrobial agent widely used in caries prevention, its influence on biofilms under sliding wear remains unknown. The main aim of this work was to assess the effect of mixed biofilms and fluoride on the tribocorrosion behavior of titanium. Streptococcus mutans and Candida albicans mixed biofilms were cultured for 8 days on ground and polished commercially pure titanium. Biofilms formation was influenced by topography: higher roughness surfaces presented higher levels of biomass. Reciprocating sliding tests were performed on both surfaces, with and without biofilms, immersed in artificial saliva in the absence or presence of fluoride (30 and 227 ppm F). The low friction coefficient registered indicated the lubricating effect of biofilms on titanium surfaces. Fluoride was also found to have lubricating properties on titanium during sliding, probably due to the precipitation of calcium fluoride (or like) salts. The presence of fluoride influenced the biotribological behavior of titanium surfaces covered with biofilms, facilitating their structural disruption and detachment. Nevertheless, open circuit potential tests reduced the corrosion of titanium in the presence of fluoride (227 ppm F) and biofilms. In conclusion, it is highlighted that fluoride interaction with biofilms can significantly influence the tribological properties of commercially pure titanium in the oral cavity.